The effect of flood depth on land use 2013 and 2020 in flood inundation mapping at Kuala Nerang, Kedah / Siti Noor Amira Ismail - Ismail, Siti Noor Amira (2021)
The most destructive natural catastrophe in Malaysia has been flooded. In 2010, heavy rainfall in North Peninsular Malaysia caused flooding in early November. In the states of Perlis and Kedah, are the worst hit areas. The selected study area is Sungai Padang Terap, Kedah because during the 2010 flood the area was most affected. Disaster prevention is increasingly necessary due to the rising environmental threats created by climate change. Then, this study aims to analyze the effect of DEMs on Flood Inundation Mapping and there were two objectives of this study, i) to generate flood depth map and ii) to compare the effect of manning value to the flood depth using different DEM. This study applied a method by generate flood inundation map using IFSAR DEM for 2010, and for land use classification are using image satellite data for the year 2013 and 2020 and generate the land use map by using ArcMap software meanwhile flood map is generated by using HEC-RAS. The Steady flow analysis was used to generate flood model with the Manning n value. The result is expected to predict the effect of flood depth on land use in Flood Inundation Mapping and will beneficially by providing more understanding information related to the flood.